2012
DOI: 10.5850/jksct.2012.36.5.549
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Influences of Appearance and Body Image on Appearance Enhancement Behavior

Abstract: This study investigates the effects of sociocultural influences and body image on appearance enhancement behaviors (facial management, clothing selection, and weight/figure management). For data collection, a questionnaire was administrated to 562 female college students in Gwangju City, Chonnam area and Chonbuk area, Korea, from May 23 to June 10, 2011. To analyze the data, a SPSS 18.0 statistics package was used, and descriptive statistical analysis, frequency analysis, factor analysis, reliability analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Three Korean language studies examined parental and peer influences on body image. Kim (2014a) and Kim and Hwang (2008) found a negative direct effect between parental and peer attitudes toward appearance and body satisfaction, whereas Park and Chung (2012) found a positive direct effect between parental and peer attitudes toward appearance and appearance concern. These findings indicate that the more parents and peers engaged in appearance management behaviors, held appearance in high regard, and desired the thin-ideal, the less body satisfaction and more appearance concern participants reported.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Three Korean language studies examined parental and peer influences on body image. Kim (2014a) and Kim and Hwang (2008) found a negative direct effect between parental and peer attitudes toward appearance and body satisfaction, whereas Park and Chung (2012) found a positive direct effect between parental and peer attitudes toward appearance and appearance concern. These findings indicate that the more parents and peers engaged in appearance management behaviors, held appearance in high regard, and desired the thin-ideal, the less body satisfaction and more appearance concern participants reported.…”
Section: Resultsmentioning
confidence: 98%
“…Seven Korean language studies examined appearance management behaviors (e.g., make-up and cosmetics, fashion and clothing, hair and body care). Four of the seven studies found that appearance concern or stress positively predicted appearance management behaviors (Jun & Lee, 2014; Lee & Ku, 2009; Park & Chung, 2012; Seo, 2014). Two of the seven studies found that body satisfaction negatively predicted appearance management behaviors (Kim, 2014a; Lee & Cho, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…또한 화장행동은 자신을 중심으로 한 특성과 타인 또는 사회를 중심으로 한 특성 모두를 갖는 활동으로 상호작용 을 통해 동조행동으로 나타나며 (Lee, 2002;Park, 2003;Cash & Cash, 1982) (Lee, 2007;Graham & Jouhar, 1983). 화 장행동의 범위는 최근 매스미디어의 발달로 개인의 개성 및 다 양성을 중시하게 되면서 외모를 아름답게 가꾸는 행위를 넘어 서 타인과의 관계를 고려하는 사회적 행위로 확장되고 있어 (Park, 2002;Youn, 2009) (Graham & Jouhar, 1983) (Choi et al, 2002). 화장품 은 학자들마다 용도별, 상태별, 제조별로 분류하고 있으며 (Hwang, 2019) 이 중 색조화장품은 유형별로 베이스 메이크업 (base make-up)화장품과 포인트 메이크업(point make-up)화장 품으로 나누어 살펴볼 수 있다 .…”
Section: 화장행동은 자기 스스로 신체를 깨끗이 가꾸고 색조화장을unclassified